Associations of sleep duration and sleep quality with life satisfaction in elderly Chinese: The mediating role of depression. (July 2016) - Zhi, Ting-Fan; Sun, Xun-Ming; Li, Shu-Juan; Wang, Qun-Shan; Cai, Jian; Li, Lin-Zi; Li, Yan-Xun; Xu, Min-Jie; Wang, Yong; Chu, Xue-Feng; Wang, Zheng-Dong; Jiang, Xiao-Yan
Highlights: Individuals who slept ≤6 h per night (OR = 2.67, 95% CI 1.88–3.79) and who slept poorly (OR = 2.91, 95% CI 2.16–3.91) were more likely to suffer from life dissatisfaction compared with those who slept 7–8 h among Chinese adults aged 70–84 years. The aforementioned associations were partially mediated by depression, with mediating effects of 13.9% and 13.3% for short sleep duration and sleep quality, respectively. Appropriate sleep duration and good sleep quality are beneficial to LS among older adults. Reducing the occurrence of depression, an additional goal of maintaining a good sleep status, also improves LS. Abstract: This study investigated whether sleep duration and quality were related to life satisfaction (LS) among older Chinese adults and whether depression mediated those relationships. Cross-sectional data from the aging arm of the Rugao Longevity and Aging Study were used. Sleep duration, sleep quality, depression, LS and covariates were analyzed using logistic regressions. To assess the potential mediation of depression on the association between sleep duration and quality and LS, Aroian tests were used. Of 1756 older Chinese adults aged 70–84 years, 90.7% of the men and 83.3% of the women reported being satisfied with their lives. After adjusting for covariates, older adults who slept ≤6 h per night were more likely to suffer from life dissatisfaction compared with those who slept 7–8 h (OR = 2.67, 95% CI 1.86–3.79), and individuals who slept poorly were almost 2 times (OR = 2.91, 95% CI 2.16–3.91) more likely to have life dissatisfaction. The Aroian tests confirmed that these relationships were partially mediated by depression (p < 0.001). Between short sleep and LS, the mediating effect of depression accounted for 13.9% of the total effects. Moreover, the mediating effect of depression on the association between sleep quality and LS was 13.3%. Short sleep duration and poor sleep quality were inversely associated with LS, and the relationships were partially mediated by depression. Our study suggests that both sleep and depression status are important factors for LS among the elderly.